The new era of water resources management: from "dry" to "wet" water savings - Seckler, D. (International Irrigation Management Institute, 1996)
Examines the concept of water efficiency, the impact of water recycling and implications for water management. Distinguishes between "wet" and "dry" water savings, and explores opportunities for creating "wet" savings-savings that make more water available for use in a basin.